Effect on Each Step Strategy of Donation by DIP in Korea. (July 2018) - Kwon, Jiyoun; Kim, Kyoungmin; Noh, Eunjeong; Ju, Yongho; Heo, Sujin; Lee, Hwajeong; Kang, Hyunjin; Kim, Sunhee; Cho, Wonhyun
Abstract : Background: The Donation Improvement Program(DIP) of KODA has been done to increase organ donation at each hospital. Increasing numbers of reporting potential donor between 2015 and 2016 were 2.57/per DIP hospital and 0.15/per non DIP hospital. We want to review the changes in the program each step of donation program and implement them for future development of DIP. Methods: In order to evaluate the effectiveness of DIP in each hospital, we analyzed the results of medical record review(MRR) which were conducted at 6 months before agreement of DIP, 6 months and 1-year interval after agreement. MRR were done in total 34, 814 cases between 1st Jan 2012 to 30th June 2017 about detect recognition, approach and donation rate of each center. Hospital Attitude Survey was performed also. The degree of recognition, attitude and knowledge related to brain death and organ donation have been analyzed from HAS data. Responders were 948 hospital staffs from 23 DIP hospitals in 2012 and 1, 959 hospital staffs from 44 DIP hospitals in 2017. Results: MRR reviewed the identification rate of potential brain death were 24.3%, 61.4% respectively, 6 months before agreement, 6 months and 1 year interval after agreement. And Approach rate of each period were 13.3%, 33.2% respectively. Donation rate of each period were 7.4%, 12% respectively. Hospital staffs who had the necessary competence or necessary knowledge to refer a potential donor was 40.4% in 2012, while it increased up to 61.5% in 2017. Those who answered 'Have education experience about brain death' increased markedly from 20.1% to 30.2%. In 2017, when explaining donation, 86.4% of the respondents said that the separation of the medical staff and the coordinator had a positive effect on the donation consent. Conclusions: DIP has a positive effect in increasing the identification rate as medical staff' educational experience increases. And the necessary competence or necessary knowledge to refer a potentail donor also increased. It was confirmed that there was a positive effect on consent for separating the interviews between the medical staff and the coordinator. As a result, the longer the duration of application for strengthening each stage of donation in the DIP, the higher the identification and donation rate.